BJPsych Open: celebrating 10 years of publishing excellence: a decade in review - Kenneth R. Kaufman (BJPsych Open)
In celebrating the 10th anniversary of BJPsych Open, this editorial review serves as a personal reflection and an overview of the birth, growth, expansion and excellence of the Journal as well as an introduction to the BJPsych Open 10th Anniversary Thematic Series. Specific emphasis is placed on changes and advances in productivity, the editorial board, publishing, thematic series, topical articles and focus on ethics. Further, articles of importance to our stakeholders are noted (top cited/downloaded, highlighted articles, articles of the month). The remit and vision for BJPsych Open remains unchanged: a general psychiatric journal with high-quality, methodologically rigorous and relevant publications, with relevance to the advancement of clinical care, patient outcomes, the scientific literature, research and policy. The Journal’s continued quality, growth and international recognition speak to its place in scientific literature, to the RCPsych mission to disseminate knowledge and to its bright future. As Editor-in-Chief, I note the debt of gratitude owed to an exemplary multidisciplinary team and the honour and privilege of serving in this role.